Gender classification in Bangla language using deep learning-based voice analysis - Hakim, Talukder Juhaer; Monsur, Sayema Binte; Shuvo, Abtahi Maskawath; Azrine, Tasmia; Labib, Md. Zarif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.